Evaluation of Hypovitaminosis D in different age and gender groups in Khyber Pakhtunkhwa Pakistan - Sajid Ali, Muhammad Zubair, Ahmad Shamim Khan, Sidra Zaman, Alishba Ali, Sawera Iftikhar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hypovitaminosis D is associated with many chronic disorders such as cancer, osteoporosis, cardiovascular, rickets, and musculoskeletal disorders. Therefore, this study was designed to determine the level of vitamin D in our region. Methods: A total of one hundred and ninety-five adult participants were enrolled. Patients were referred by medical physicians and consultants after identifying the sign and symptoms of Hypovitaminosis D. Both male and female gender were recruited and patients with severe chronic disorders were excluded from the study. Vitamin D levels were categorized into four groups including deficiency of vitamin D (<10 IU), insufficient vitamin D level (10-30 IU), Normal vitamin D level (30-100 IU), and Hypervitaminosis level of vitamin D (>100 IU). Results: The minimum and maximum age of the patient was 17 and 57 years age with the mean age of all patients being 33.833.8+17.3. Male and female patients were 79.5% (n=155) and 20.5% (n=40). The highest number of patients were identified in the age group 36-45 years. Vitamin D level was found in 7.7% deficient while insufficiency of vitamin D was found in 48.7%. Insufficiency of vitamin D was found more in female (67.5%) patients than in males (43.9%). The highest prevalence of vitamin D insufficiency was obtained in the age group 16-25 years. No patient was found with hypervitaminosis D. Conclusion: There is a high deficiency of vitamin D in patients particularly in females and younger age populations. Awareness about vitamin D importance, psychosocial intervention, and vitamin D supplementation should be implemented to prevent any severe consequences of Hypovitaminosis D.